2015
DOI: 10.1007/s13277-015-3432-0
|View full text |Cite
|
Sign up to set email alerts
|

ShRNA-mediated knock-down of CXCR7 increases TRAIL-sensitivity in MCF-7 breast cancer cells

Abstract: This study aims to investigate the effects of CXCR7-shRNA on TRAIL-mediated apoptosis and suppression of invasive migration and the underlying mechanisms. (1) We constructed CXCR-7-shRNA lentiviral vectors and confirmed their silencing efficiency in MCF-7 cells by RT-PCR analysis. (2) The effects of CXCR7 and/or TRAIL on cell proliferation were examined by MTT assay. (3) Trans well invasion assay was used to examine the effects of CXCR7 silencing and/or TRAIL on MCF-7 cell invasive migration. (4) Expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…CXCR7 overexpression reduces the apoptotic fraction in prostate cancer cells and protects these cells from apoptosis (Wang et al, 2008a). Likewise, knockdown of CXCR7 in the MCF7 breast cancer cell line increased the expression of the proapoptotic caspase three and eight proteins (Gao et al, 2015).…”
Section: C-x-c Motif Chemokine Ligand 12 Axis In Tumor Cell Growth Anmentioning
confidence: 99%
“…CXCR7 overexpression reduces the apoptotic fraction in prostate cancer cells and protects these cells from apoptosis (Wang et al, 2008a). Likewise, knockdown of CXCR7 in the MCF7 breast cancer cell line increased the expression of the proapoptotic caspase three and eight proteins (Gao et al, 2015).…”
Section: C-x-c Motif Chemokine Ligand 12 Axis In Tumor Cell Growth Anmentioning
confidence: 99%
“…ACKR3 promotes cancer cell growth, inducing ERK1/2 phosphorylation and inhibiting apoptosis in breast cancer [72]. In breast and prostate cancer, ACKR3 forms heterodimers with EGFR and stimulates its signaling promoting tumor-cell proliferation in a ligand-independent manner [73][74][75].…”
Section: Ackr3/cxcr7mentioning
confidence: 99%
“…Decreasing ACKR3 levels alters expression of cell cycle-related proteins and leads to cell cycle arrest, hence reducing cell proliferation (Salazar et al, 2014). Additionally, knock down of the receptor in the MCF7 breast cancer cell line increased the expression of the proapoptotic caspase 3 and 8 proteins (Gao et al, 2015). In addition, ACKR3 expression enhances breast cancer proliferation through signal transducer and activator of transcription 3 activation, which has previously been linked to apoptosis resistance and cell cycle progression in invasive breast cancer (Wani et al, 2014;Li et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
“…Several in vitro and in vivo studies have found that higher levels of ACKR3 result in increased cell proliferation and invasive migration, promoting tumor growth and metastasis (Miao et al, 2007;Xue et al, 2013;Gao et al, 2015;Li et al, 2015). However, the molecular mechanisms linking enhanced ACKR3 expression to these processes are not fully elucidated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation